2010
DOI: 10.1111/j.1469-1795.2009.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Dry season habitat use by critically endangered white‐shouldered ibis in northern Cambodia

Abstract: We present the first scientific study of white-shouldered ibis Pseudibis davisoni habitat preferences in dry dipterocarp forest. Foraging sites included seasonal pools, forest understorey grasslands and fallow rice fields, with terrestrial sites used more following rainfall. Habitat and anthropogenic effects in logistic models of foraging site selection were examined by multimodel inference and model averaging. White-shouldered ibis preferred pools with greater cover of short vegetation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Its populations are small and declining, with ~200 individuals remaining across a small number of protected areas [ 36 ]. The giant ibis relies on deciduous dipterocarp forests and waterholes for forage in the shallow water and saturated mud [ 37 ]. The birds breed during the wet season, pairing and nesting between June and September [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Its populations are small and declining, with ~200 individuals remaining across a small number of protected areas [ 36 ]. The giant ibis relies on deciduous dipterocarp forests and waterholes for forage in the shallow water and saturated mud [ 37 ]. The birds breed during the wet season, pairing and nesting between June and September [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Currently available data provide preliminary results that ongoing surveys (conducted until 2011) will confirm. White‐shouldered Ibis appear to stop visiting seasonal pools in the forest after the first rains in April/May (Wright et al. 2009).…”
Section: Implementation and Findingsmentioning
confidence: 99%
“…Deciduous dipterocarp forests are also highly seasonal habitats, experiencing 5–6 months of drought per year (Miles et al, 2006). In such dry tropical habitats, water and food resource availability may be limiting factors for the distributions, movements and home ranges of many species during the dry season (Aung et al, 2001; Redfern et al, 2003), and waterholes are likely to be a substantial component of water surface availability, providing important water resources and foraging habitat for many species (Keo, 2008; Wakefield et al, 2008; Wright et al, 2010; Wright et al, 2012). Utilization of waterholes by wildlife is also likely to be higher during the dry season (Wakefield et al, 2008; Wright et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…During the dry season water availability is mainly limited to perennial rivers and waterholes, which are an essential part of the forest and are used by several of these threatened large species (Keo, 2008; Wright et al, 2012; Gray et al, 2015b). However, little is known about the relationship between wildlife and waterholes in South-east Asian deciduous dipterocarp forests with the exception of two studies on the giant and white-shouldered ibises (Wright et al, 2010, 2012). Although these studies suggested waterholes are important for these two species, it is largely unknown how they impact the other threatened species in this landscape and, for example, how the morphological characteristics of the waterholes affect usage.…”
Section: Introductionmentioning
confidence: 99%